Gejala Urban Sprawl Sebagai Pemicu Proses Densifikasi Permukiman di Daerah Pinggiran Kota (Urban Fringe Area) Kasus Pinggiran Kota Yogyakarta - Sri Rum Giyarsih (Journal of Regional and City Planning, 2001)
The impact of urban development is the tendency of the shift of urban functions shift to urban fringe area that is called urban sprawl. The phenomenon of urban sprawl in urban fringe area has resulted in land conversion process from agriculture to non-agriculture. Furthermore, this conversion of agriculture land to non-agriculture land will result in settlement desification process in urban fringe area. This process that happens in urban fringe area is a respond to increasing demand of space in urban area. In turn, the spatial transformation will be followed by socio-economic, cultural, and physical environment transformation process.